Longevity of insulin receptor substrate1 null mice is not associated with increased basal antioxidant protection or reduced oxidative damage - Page, Melissa M. (Springer Netherlands, 2012)
Insulin receptor substrate-1 null (Irs1(−/−)) mice are long lived and importantly they also demonstrate increased resistance to several age-related pathologies compared to wild type (WT) controls. Currently, the molecular mechanisms that underlie lifespan extension in long-lived mice are unclear although protection against oxidative damage may be important. Here, we determined both the activities of several intracellular antioxidants and levels of oxidative damage in brain, skeletal muscle, and liver of Irs1(−/−) and WT mice at 80, 450, and 700 days of age, predicting that long-lived Irs1(−/−) mice would be protected against oxidative damage. We measured activities of both intracellular superoxide dismutases (SOD); cytosolic (CuZnSOD) and mitochondrial (MnSOD), glutathione peroxide (GPx), glutathione reductase (GR), catalase (CAT), and reduced glutathione (GHS). Of these, only hepatic CAT was significantly altered (increased) in Irs1(−/−) mice. In addition, the levels of protein oxidation (protein carbonyl content) and lipid peroxidation (4-hydroxynonenal) were unaltered in Irs1(−/−) mice, although the hepatic GSH/GSSG ratio, indicating an oxidized environment, was significantly lower in long-lived Irs1(−/−) mice. Overall, our results do not support the premise that lifespan extension in Irs1(−/−) mice is associated with greater tissue antioxidant protection or reduced oxidative damage.